2023
DOI: 10.1002/jobm.202300141
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between systemic diseases and oral microbiota shifts in the aging community: A narrative review

Seyed Ali Mosaddad,
Pegah Mahootchi,
Sajedeh Safari
et al.

Abstract: As a gateway to general health and a diverse microbial habitat, the oral cavity is colonized by numerous microorganisms such as bacteria, fungi, viruses, and archaea. Oral microbiota plays an essential role in preserving oral health. Besides, the oral cavity also significantly contributes to systemic health. Physiological aging influences all body systems, including the oral microbial inhabitants. The cited effect can cause diseases by forming dysbiotic communities. Since it has been demonstrated that microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 162 publications
0
9
0
Order By: Relevance
“…In contrast, younger patients with T2DM in China displayed a significantly greater abundance of Proteobacteria compared to Firmicutes [ 2 ]. This may be related to the fact that aging leads to a dysfunctional adaptive immune response that affects the salivary microbiome [ 5 , 27 ]. Omori et al [ 5 ] reported a significant increase in the abundance of Firmicutes in a diabetic group compared with a healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, younger patients with T2DM in China displayed a significantly greater abundance of Proteobacteria compared to Firmicutes [ 2 ]. This may be related to the fact that aging leads to a dysfunctional adaptive immune response that affects the salivary microbiome [ 5 , 27 ]. Omori et al [ 5 ] reported a significant increase in the abundance of Firmicutes in a diabetic group compared with a healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue engineering is essential in expediting the evolution of components that facilitate the reconstruction of damaged or lost tissue. Numerous studies have reported that PBMT contributes to tissue regeneration by exerting biological modulatory effects on cell differentiation, improving the healing of fractures, regenerating periodontal tissue, promoting implant osseointegration, and facilitating bone reconstruction 104,105 . These effects have been observed both with and without the utilization of biomaterials.…”
Section: Pbm Therapy In Maxillofacial Regenerationmentioning
confidence: 99%
“…Periodontitis is caused by gram‐negative obligate anaerobes [39]. The oral cavity is infected with gingivitis when gram‐positive bacteria produce destructive metabolites [86, 87]. Inflammation of the gums leads to periodontal disease through gingivitis [72].…”
Section: The Antimicrobial Effect Of Photodynamic Therapymentioning
confidence: 99%